The Cultural Da'wah Method of Rapai Geleng During The Golden Ege: An Analytical Approach to Islamic Religious Education in Aceh - Al Fazzatil A'la; Al Farahil A’la (Journal of Islamic Education and Ethics, 2023)
Islamic religious education is an important part of developing spirituality and religious understanding for individual Muslims. The approach to Islamic religious education has experienced significant development through the application of cultural da'wah methods. The Cultural Da'wah method is a combination of da'wah models that include elements of culture, religion, art, motion and sound. In the culture and customs of the Acehnese people, the Rapai gelling dance is one of the cultural da'wah media used to convey Islamic da'wah. This study aims to analyze and explore the approach of Islamic religious education through the cultural da'wah method of Rapai Geleng during the Golden Age of An-Nur PAUD students in Seuneulop Village, Southwest Aceh. The research method used in this study is qualitative research with a case study approach. Data were collected through participatory observation, interviews, and analysis of related documents. The results showed that the approach of Islamic religious education through cultural da'wah methods during the Golden Age at PAUD An-Nur Seuneulop Village had a positive impact on children's religious understanding and character development. The method of cultural da'wah is able to create a fun, creative, and local culture-based learning environment, which effectively increases interest in learning and understanding Islam. In addition, this study also reveals that this approach has advantages in combining religious values with local culture, thus enriching the understanding of Islam holistically. An-Nur ECCE teachers have an important role in implementing this approach by utilizing various media and activities that are appropriate to the local cultural context. The results of this research make an important contribution to the development of Islamic religious education approaches through cultural da'wah methods during the Golden Age.